2016
DOI: 10.1111/cgf.12784
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Visualization for Live Cell Imaging

Abstract: Live cell imaging is an important biomedical research paradigm for studying dynamic cellular behaviour. Although phenotypic data derived from images are difficult to explore and analyse, some researchers have successfully addressed this with visualization. Nonetheless, visualization methods for live cell imaging data have been reported in an ad hoc and fragmented fashion. This leads to a knowledge gap where it is difficult for biologists and visualization developers to evaluate the advantages and disadvantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 81 publications
(392 reference statements)
0
18
0
Order By: Relevance
“…Thus, from the systems review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] we see that these software products contain summary statistical data on quantitative indicators. They focused on providing only key parameters of the education system and do not allow in-depth analysis.…”
Section: Literature and Systems Reviewmentioning
confidence: 99%
“…Thus, from the systems review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] we see that these software products contain summary statistical data on quantitative indicators. They focused on providing only key parameters of the education system and do not allow in-depth analysis.…”
Section: Literature and Systems Reviewmentioning
confidence: 99%
“…To date, most of the interactive tasks that are supported by visualization tools allow users to perform simple visual representation manipulations (e.g., panning and zooming) and selection of model choices (e.g., selecting Naïve-Bayes or Support Vector Machine technique). In a recent survey of biomedical visualizations, it was observed that tools typically offer interactions like rotating and zooming but provide limited support for querying and other more advanced interactive tasks [8]. Ko et al conducted a survey of visualizations for financial data and noted that most visualizations failed to support tasks such as exploring, annotating, and linking [16].…”
Section: Interactionmentioning
confidence: 99%
“…Interactive visualizations, when properly designed, can provide a means for analyzing and exploring large sets of data. Interactive visualizations can help maintain context during exploration, support the identification of patterns, and facilitate a wide variety of tasks in which users engage [8,9]. When involved in data-driven efforts, the tasks that users perform are mostly non-routine, exploratory, and interrelated [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general paradigm for the analysis of such data is centered on the extraction of information from the cell lineage of all visible cells, for example in the studies by Schneider et al ( 2012 ) and Helfrich et al ( 2015 ), which ultimately leads to its visualization, as described in the study by Pretorius et al ( 2016 ). A cell lineage is a sequence of cells that have developed from a common ancestor.…”
Section: Introductionmentioning
confidence: 99%